Thyroid Hormones, Peripheral White Blood Count, and Dose of Basal Insulin Are Associated with Changes in Nerve Conduction Studies in Adolescents with Type 1 Diabetes - Marta Wysocka-Mincewicz; Marta Baszyńska-Wilk; Maria Mazur; Aleksandra Byczyńska; Monika Nowacka-Gotowiec (Metabolites, 2021)
Type 1 diabetes (T1D) in the child population is the third most common chronic disease. Diabetic peripheral neuropathy (DPN) is a very disabling and silently developing complication. This prospective, observational study enrolled 182 (93 girls) patients with T1D, aged 16.5–18 years. The aim of the study was to assess the correlation between factors of diabetes metabolic control, blood count, thyroid hormones, thyroid-stimulating hormone (TSH), level of cortisol, vitamin D3, metabolic factors, demographic data, and nerve conduction study (NCS) parameters. We revealed that in multivariate regression models for almost all NCS parameters, beside height and diabetes duration, significant factors were basal insulin dose per kilogram of weight (BID/kg), body mass index (BMI), and thyroid hormones. For conduction velocities of the motor nerves, mean HbA1c exists in models. In all models for all NCS parameters there exists at least one parameter of peripheral white blood cell counts (predominantly monocytes). There is a significant influence of thyroid hormones, peripheral blood white cells count, and BID per weight on parameters of NCS. It is essential to take care of the proper insulin dose per weight of patients and the adequate proportion of basal to prandial insulin.